Conceptual Structures: Leveraging Semantic Technologies 17th International Conference on Conceptual Structures, ICCS 2009, Moscow, Russia, July 26-31, 2009. Proceedings - Rudolph, Sebastian.; Dau, Frithjof.; Kuznetsov, Sergei O. (Lecture Notes in Computer Science, 2009)
This book constitutes the refereed proceedings of the 17th International Conference on Conceptual Structures, ICCS 2009, which took place in Moscow, Russia, on July 26-31, 2009. The 18 papers presented together with 5 invited contributions were carefully reviewed and selected from approximately 50 submissions. Originally centered around research on knowledge representation and reasoning with conceptual graphs, over the years ICCS has broadened its scope to include innovations from a wider range of theories and related practices, among them other forms of graph-based formalisms like RDF or existential graphs, formal concept analysis, semantic Web technologies, ontologies, concept mapping and more.